Roadmapping as an Instrument for the Sustainable Development Planning of Amalgamated Territorial Communities - Ustymenko, Volodymyr; Hrechana, Svitlana; Kuzmenko, Olena; Busarieva, Tetiana; Zablodska, Daria (European Journal of Sustainable Development, 2019)
In the context of decentralization reform, the use of roadmapping has the particular importance for the development of amalgamated territorial communities. This visual and understandable tool for strategic planning is widely used around the world, but in Ukraine it has not become quite popular, including due to the lack of regulatory and methodological support. This article was an attempt to change this negative trend, as it proves the feasibility of roadmapping use in the planning of sustainable development of amalgamated territorial communities and offers a unified procedure for the construction of such a road map in accordance with the existing legal framework. Attention is focused on the fact that the use of any from these methods of prediction in the amalgamated territorial communities at this stage of decentralization is associated with a significant number of problems. To improve the quality of community planning and overcome the shortage of skilled and professional staff was suggested to use the roadmapping as a process of building a kind of guide-guide or step-by-step scenario of AT? development with reflection in the graph form of strategically important events in the time sequence is proposed. It is stated that the roadmaps have significant advantages, the main of which is the visibility and clarity and are represented by a wide range of types and formats. It is proved the appropriateness of technology roadmaps usage as such, let to associate time-specific measures of development, to assess threats and opportunities, identify priorities. Proposed procedure for constructing the roadmap for the sustainable development of A?? with detailed description of each stage and a list of possible key points (nodes of the graph), which are fully correspond to the official methodological content of strategic planning of local and regional developments. Its implementation should help amalgamated communities not only to improve the quality of strategic plan and simplify its complex process, but also ensure its compliance with the current regulatory framework. Keywords: roadmapping, sustainable development, amalgamated territorial community, decentralization, strategic planning, procedure for constructing the technology roadmap.